A Generalist Approach in Social Work Education in Turkey - Işıl Bulut (Social Work and Society)
A global review of social work education reveals considerable similarity among countries as well as significant differences. Historically, programs of social work education are informed by humanistic values and encompass knowledge of social problems, an understanding of individuals and their environment in interaction, and method of intervention into social and human difficulties. At the same time, structure of social work within the educational system and the length of training vary considerably from country to country. There is no serious international standards’ setting for social work education, programs, educators and students around the world. Education programs exist at differing levels of education and for differing periods of time. There are no worldwide data on the number and qualifications of teachers of social work, the number and characteristics of social work students, variations in curricula and type of practicum (Hokeenstad and Kendall 2001; Hokenstad and Midgley 1998). North American and European models have had a major influence on social work educational programs in most parts of the world, especially developing countries. Still, the amount of western influence on social work education in developing countries is an issue that continues to be discussed (Hockenstad, Khinduka and Midgley 1992; Frumkin and Lloyd 2001). The programs in practice in Europe and North America have influenced the implementation of social work education programs. In recent years this influence has had a big part in the acceptance of the generalist approach. It is very important that social work education programs must be planned in accordance with the social structure and the development process of the society. Because of this, information on the social indicators and social welfare services will be given first then social work education will be stressed upon.